2020
DOI: 10.1111/jcpt.13218
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of genotype‐guided warfarin anticoagulation in Chinese elderly patients with nonvalvular atrial fibrillation

Abstract: What is known and objective Warfarin is an oral anticoagulant which has been widely used to treat and prevent thromboembolic events. Managing warfarin therapy requires careful monitoring and dose titration. This randomized controlled study was designed to assess the effect of genotype‐guided warfarin anticoagulation in Chinese elderly patients with nonvalvular atrial fibrillation. Methods 507 adults were randomized to receive initial dosing as determined by an algorithm containing genetic (VKORC1 and CYP2C9) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…A further 46 studies were then excluded due to their inclusion of AF patients with other comorbidities or trials that were incomplete. Ultimately, a Meta-analysis was conducted with 11 studies, all of which were RCT [13,21,22,23,24,25,26,27,28], encompassing 70,801 patients comparably divided between two groups (NOACs and Warfarin). The study involved a total of 37,010 patients in the NOAC group, while the Warfarin group comprised 33,791 patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A further 46 studies were then excluded due to their inclusion of AF patients with other comorbidities or trials that were incomplete. Ultimately, a Meta-analysis was conducted with 11 studies, all of which were RCT [13,21,22,23,24,25,26,27,28], encompassing 70,801 patients comparably divided between two groups (NOACs and Warfarin). The study involved a total of 37,010 patients in the NOAC group, while the Warfarin group comprised 33,791 patients.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining two trials were solely focussed on Warfarin. Zhu Y et.al [25] demonstrated 0.98% stoke rate and 3.55 % bleeding rate, whereas JG Cho et.al [24] showed 1.29 % stoke rate and 1.46 % bleed rate.…”
Section: Discussionmentioning
confidence: 97%
“…In this trial that recruited Chinese patients with heart valve replacement, genotype-guided dosing reduced the number of days to reach therapeutic INR (genotype-guided dosing vs. clinically-guided dosing, 3.8 ± 2 vs. 4.4 ± 2, p < 0.001) although there was no reduction in major bleeding or thrombotic events. Two other recent relatively-large trials, respectively, randomized 660 and 507 patients and both reported that genotype-guided dosing was better than clinically-guided dosing in terms of the PTTR [respective mean differences 5.6 (95% CI 1.1 to 10.2, p = 0.01) and 17.4 (95% CI 11.8 to 22.9, p < 0.01)] ( Zhu et al, 2020b ; Guo et al, 2020 ). These trials together with other Chinese trials recruited 4,858 patients or 88% of all Asian participants meaning other Asian countries/non-Chinese populations are currently underrepresented.…”
Section: Clinical Utility Studiesmentioning
confidence: 99%
“…Despite extensive researches, warfarin dosing and its relationship with gene polymorphisms remain an unresolved problem in China [9].Genotype-guided warfarin dosing that could improve the average TTR were published in 2020, however, there is still no nal consensus yet on the bene ts of genotype-guided warfarin dosing in clinical practice and the guide for the use of genotypeguided warfarin dosing in patients for the treatment of AF is still lacking. Larger clinical studies are still required to validate whether genotype-guided dosing improves such outcomes [10]. Therefore, we assessed two genes (CYP2C9*3 and VKORC1c.1639G > A) which may in uence warfarin drug response and evaluate whether genotype-guided warfarin dosing is superior to routine clinical use in Chinese patients with nonvalvular AF.…”
Section: Introductionmentioning
confidence: 99%